2016
DOI: 10.1103/physrevlett.117.206802
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Hyperfine, Spin-Orbit, and Decoherence Effects in a Pauli Spin Blockade

Abstract: We detect in real time inter-dot tunneling events in a weakly coupled two electron double quantum dot in GaAs. At finite magnetic fields, we observe two characteristic tunneling times, T d and T b , belonging to, respectively, a direct and a blocked (spin-flip-assisted) tunneling. The latter corresponds to lifting of a Pauli spin blockade and the tunneling times ratio η = T b /T d characterizes the blockade efficiency. We find pronounced changes in the behavior of η upon increasing the magnetic field, with η i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 61 publications
(85 reference statements)
0
32
0
Order By: Relevance
“…Also, our values of T 1 are about four orders of magnitude shorter than those in electronic GaAs dots at equivalent magnetic fields. Again, this is a consequence of much weaker SOI in the electronic systems 18,[57][58][59] and a strongly elongated shape of our dot 48 , which is known to enhance the spin-orbit coupling 21 . However, extrapolation of our values of T 1 to very low magnetic fields promises superior lifetime of the hole spin over that of the electron owing to the much weaker hyperfine interactions.…”
Section: Discussionmentioning
confidence: 93%
“…Also, our values of T 1 are about four orders of magnitude shorter than those in electronic GaAs dots at equivalent magnetic fields. Again, this is a consequence of much weaker SOI in the electronic systems 18,[57][58][59] and a strongly elongated shape of our dot 48 , which is known to enhance the spin-orbit coupling 21 . However, extrapolation of our values of T 1 to very low magnetic fields promises superior lifetime of the hole spin over that of the electron owing to the much weaker hyperfine interactions.…”
Section: Discussionmentioning
confidence: 93%
“…First, the HH in III-V materials experiences a strong spin-orbit interaction, causing the hole spin to rotate during tunneling [12,13,26]. In electronic devices this process was found to be orders of magnitude weaker [28]. One expects, therefore, that the Pauli blockade will be lifted for all (1,1)→(2,0) tunneling channels.…”
mentioning
confidence: 99%
“…While g * = 0 is desired, in practice it should be small enough for the resulting Zeeman splitting to be smaller than the photon bandwidth [6,7]. Currently the longest spin coherence times have been demonstrated for electron spin qubits in 28 Si [9], but their coupling to light is challenging due to the indirect bandgap. GaAs electronic devices, while more promising [4,5], still require g-factor engineering.…”
mentioning
confidence: 99%
“…In this work, we choose the Pauli-spin blockade (PSB) effect in a DQD [32] to investigate the charge and spin dynamics because PSB is the simplest but most significant spin-correlated phenomenon that affects the electron dynamics in a DQD. Real-time charge sensing of a DQD holding two electrons in PSB has been reported in earlier studies, which showed that the charge transitions can be classified into spin-flip and spin-conserving transitions [33][34][35]. The spin-conserving transitions only occur when the two spins are antiparallel, while the spin-flip transitions change the spin configuration.…”
Section: Introductionmentioning
confidence: 91%